Tingkat Pengetahuan Pasien Gagal Ginjal Kronik Dalam Menjalani Hemodialisa - Wiyani, Ni Putu; Sukarja, I Made; Krisnayani, Ni Made Wina; Daryaswanti, Putu Intan (Jurnal Kesehatan Medika Udayana, 2018)
ABSTRACT Background: Chronic Kidney Failure is one of the important health problems in Indonesia and the world community. In Indonesia, according to data from Penetri (Persatuan Nefrologi Indonesia) the number of patients with kidney failure is estimated at 4500 people, but those detected suffering from terminal stage chronic kidney failure from those undergoing dialysis (hemodialysis) are only around 4 thousand - 5 thousand people. Cases of kidney failure in Indonesia are still relatively high every year, because there are still many Indonesian people not maintaining their diet and health. This means that chronic kidney failure ranks as one of the highest rates of disease causing death. The purpose of this study was to describe the level of adherence to patients with chronic kidney failure in undergoing a hemodialysis program in the hemodialysis room at Sanjiwani Hospital in Gianyar. Methods: This research is a descriptive observational type. This study uses a sampling technique that is purposive sampling with a total sample of 30 people. Results: In this study the results of the rate of compliance of CRF patients with hemodialysis were 27 respondents (90%) who were obedient and non-adherent as many as 3 respondents (10%). Thus most patients with chronic renal failure adhere to undergoing hemodialysis in the hemodialysis room of Sanjiwani Hospital in Gianyar. Conclusions: The conclusion of this study is that patients with chronic renal failure are expected to seek treatment regularly in accordance with the rules set by health workers. Delay of dialysis causes pulmonary complications, seizures, decreased consciousness, severe electrolyte disturbances, heart failure, which can cause death. ABSTRAK Latar belakang: Gagal Ginjal Kronik merupakan salah satu masalah kesehatan penting di Indonesia dan masyarakat dunia. Di Indonesia menurut data dari Penetri (Persatuan Nefrologi Indonesia) jumlah penderita gagal ginjal diperkirakan mencapai 4500 orang, namun yang terdeteksi menderita gagal ginjal kronik tahap terminal dari mereka yang menjalani cuci darah (hemodialisa) hanya sekitar 4 ribu – 5 ribu orang. Kasus gagal ginjal di Indonesia setiap tahunnya masih terbilang tinggi, pasalnya masih banyak masyarakat Indonesia tidak menjaga pola makan dan kesehatan tubuhnya. Hal ini berarti membuat penyakit gagal ginjal kronik menduduki salah satu peringkat penyakit penyebab kematian tertinggi. Tujuan penelitian ini adalah untuk menggambarkan tingkat kepatuhan pasien gagal ginjal kronik dalam menjalani program hemodialisa di ruang hemodialisa RSUD Sanjiwani Gianyar. Penelitian ini merupakan penelitian jenis observasional deskriptif. Penelitian ini menggunakan teknik sampling yaitu purposive sampling dengan jumlah sampel sebanyak 30 orang. Pada penelitian ini hasil dari tingkat kepatuhan pasien GGK terhadap hemodialisa sebanyak 27 responden (90%) yang patuh dan yang tidak patuh sebanyak 3 responden (10%). Dengan demikian sebagian besar pasien gagal ginjal kronik patuh menjalani hemodialisa di ruang hemodialisa RSUD Sanjiwani Gianyar. Kesimpulan penelitian ini adalah diharapkan pasien gagal ginjal kronik agar berobat secara teratur sesuai dengan aturan yang telah ditetapkan oleh petugas kesehatan. Penundaan cuci darah menyebabkan komplikasi paru, kejang, penurunan kesadaran, gangguan elektrolit yang berat, gagal jantung, yang bisa menyebabkan kematian.